Short-term effects of air pollutants on hospital admissions for asthma among older adults: a multi-city time series study in Southwest, China - Zhang, Yuqin; Yang, Xi; Jiang, Wanyanhan; Gao, Xi; Yang, Biao; Feng, Xing Lin; Yang, Lian (Frontiers in Public Health, 2024)
This study aimed to explore the relationship between air pollution and hospital admissions for asthma in older adults, and to further assess the health and economic burden of asthma admissions attributable to air pollution.We collected information on asthma cases in people over 65 years of age from nine cities in Sichuan Province, as well as air pollution and meteorological data. The relationship between short-term air pollutant exposure and daily asthma hospitalizations was analyzed using the generalized additive model (GAM), and stratified by gender, age, and season. In addition, we assessed the economic burden of hospitalization for air pollution-related asthma in older adults using the cost of disease approach.The single pollutant model showed that every 1mg/m 3 increase in CO was linked with an increase in daily hospitalizations for older adults with asthma, with relative risk values of 1.327 (95% CI: 1.116-1.577) at lag7. Each 10 μg/m 3 increase in NO2, O3, PM10, PM2.5 and SO2, on asthma hospitalization, with relative risk values of 1. 044 (95%